Covid-19 Ultrasound image classification using SVM based on kernels deduced from convolutional neural network - DURU, ADİL DENİZ (My University, 2021)
© 2021 IEEE.Millions of people are infected daily with Coronavirus to this day, which increases deaths daily, that has made the virus an epidemic. Based on the current crisis, the availability of tool kits for test plays a significant role in fighting against Covid-19. According to less of availability tools and time consume by using traditional medical tools kit, that provide motivation for researchers to use the advantages of artificial intelligence (AI) techniques. Due to the ability of integrated with medical imaging, AI is very useful for precise diagnosis and classification for different types of diseases. However, in this study, we introduce an idea that combines a set of pre-trained deep learning convolutional neural network models with a supervised machine learning classifier, Supporting Vector Machines (SVM). The dataset used in this study was Lung ultrasound (LUS). To extract features from images, we utilized four types of CNN models namely (Resnet18, Resnet50, GoogleNet, and NASNet-Mobile). Depending on the experimental outcomes, our proposed method show outperform compared to the other latest papers published. Our results achieved based on the four types of evaluation metrics which are Accuracy, Precision, Recall, and F1-Score, where all evaluations achieved exceeded of 99%.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Kütüphanecilik; Harita Mühendisliği-Geomatik; Bilgi Sistemleri, Haberleşme ve Kontrol Mühendisliği; Kontrol ve Sistem Mühendisliği; Bilgisayar Bilimleri; Algoritmalar; Mühendislik ve Teknoloji; Social Sciences and Humanities; Sociology; Library Sciences; Geotechnical Engineering; Information Systems, Communication and Control Engineering; Control and System Engineering; Computer Sciences; algorithms; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Sosyal Bilimler (SOC); Bilgisayar Bilimi; Mühendislik; Sosyal Bilimler Genel; OTOMASYON & KONTROL SİSTEMLERİ; BİLGİSAYAR BİLİMİ, YAPAY ZEKA; TELEKOMÜNİKASYON; ALETLER & GÖSTERİM; MÜHENDİSLİK, MULTİDİSİPLİNER; MÜHENDİSLİK, ÜRETİM; BİLGİ BİLİMİ VE KÜTÜPHANE BİLİMİ; Engineering, Computing & Technology (ENG); Social Sciences (SOC); COMPUTER SCIENCE; ENGINEERING; SOCIAL SCIENCES, GENERAL; AUTOMATION & CONTROL SYSTEMS; COMPUTER SCIENCE, ARTIFICIAL INTELLIGENCE; TELECOMMUNICATIONS; INSTRUMENTS & INSTRUMENTATION; ENGINEERING, MULTIDISCIPLINARY; ENGINEERING, MANUFACTURING; INFORMATION SCIENCE & LIBRARY SCIENCE; Medya Teknolojisi; Fizik Bilimleri; Kontrol ve Optimizasyon; Enstrümantasyon; Emniyet, Risk, Güvenilirlik ve Kalite; Yapay Zeka; Bilgisayar Ağları ve İletişim; Bilgisayar Bilimi Uygulamaları; Bilgi Sistemleri ve Yönetimi; Sosyal Bilimler ve Beşeri Bilimler; Media Technology; Physical Sciences; Control and Optimization; Instrumentation; Safety, Risk, Reliability and Quality; Artificial Intelligence; Computer Networks and Communications; Computer Science Applications; Information Systems and Management; Social Sciences & Humanities